How to address the language competence form the social sciences, geography and history. A practical example in 10th grade - de la Fuente Martínez, Ángel (Avances en Supervisión Educativa, 2014)
The preparation of this paper is an approach to communicative competence from contemporary history to foster a love of reading in students of secondary education and develop other skills . It consists of six fragments of literary texts that provide insight into the peculiar revolutionary process of the Asturian industry. The literature and the novel in particular are valuable sources to enhance the development of discovery learning information; thus knowledge is built on a solid base. The proposal to solve ten school activities either as an individual or team work encourages the development of strategies that include debate, dialogue, discussion ... thereby enriching the knowledge about this historical fact , they find it appealing because has been developed in the environment. The findings of the proposed activities would be subject to a notice in the context of a school magazine.